Opportunities for Prevention and Rehabilitation Treatment of the Consequences of Perinatal Central Nervous System Damage in Premature Infants - Elena V. Pavlyukova; Irina V. Davydova; Svetlana B. Lazurenko; Galina V. Yatsyk; Olga M. Konova; Elena P. Zimina (Педиатрическая фармакология)
The socio-economic burden of the consequences of perinatal central nervous system damage in preterm infants remains an urgent healthcare issue. The review discusses the modern concepts of cerebral ischemia pathogenesis in prematures, the peculiarities of diagnosing structural brain lesions, and the ability to predict motor deficits in the future. The possibilities of assessing mental, motor development and social adaptation disorders of premature infants with consequences of perinatal pathology in the early stages of ontogenesis are described.. The modern views on rehabilitation and restorative treatment of premature infants with combined perinatal pathology are highlighted. The characteristics of non-invasive methods for early diagnosis of central nervous system pathology and therapeutic methods with the rationale for choosing preventive and curative measures and the further prediction of the disease course and outcome are given. The world experience of multidisciplinary rehabilitation of premature infants with combined perinatal pathology is highlighted.